Pengaruh Pendidikan Kewirausahaan terhadap Kesiapan Kerja Mahasiswa - Mursidin, Mursidin; Najmah, Navisah Nur; Yulianti, Ninda Aulia; Adzkia, Nur Maulani (STKIP PGRI SITUBONDO, 2024)
This study examines how entrepreneurship education affects the work readiness of PAI students in the 2022UIN Sunan Gunung Djati Bandung class of 2022. The background of this study is a field fact in which students' level of work readiness is low, which is characterized by lack of self-confidence, technical ability, and interpersonal skills. This study utilized a descriptive quantitative approach by using the explanatory survey method as part of the research approach. The study involved 75 students selected through simple random sampling method from a total population of 256. After the data was collected through a Likert scale questionnaire, statistical testing was conducted in the form of classical assumptions for simple linear regression test prerequisites with the help of SPSS 27. The results showed that entrepreneurship education and students' work readiness had a strong relationship, where R was 0.762. In addition, from the linear regression test, it was found that entrepreneurship education contributed 58.1% to students' work readiness. The results of this study confirm that entrepreneurship education is able to bridge the gap that exists between the academic world and the world of work.